Total synthesis of rapamycin. - Ley, S; Tackett, M; Maddess, M; Anderson, J; Brennan, P; Cappi, M; Heer, J; Helgen, C; Kori, M; Kouklovsky, C; Marsden, S; Norman, J; et al. (2009)
For over 30 years, rapamycin has generated a sustained and intense interest from the scientific community as a result of its exceptional pharmacological properties and challenging structural features. In addition to its well known therapeutic value as a potent immunosuppressive agent, rapamycin and its derivatives have recently gained prominence for the treatment of a wide variety of other human malignancies. Herein we disclose full details of our extensive investigation into the synthesis of rapamycin that culminated in a new and convergent preparation featuring a macro-etherification/catechol-templating strategy for construction of the macrocyclic core of this natural product.